(untitled) (Polifonia, 2012)
Neste artigo apresentamos resultados de uma pesquisa sobreformação reflexivo-crítica, envolvendo três professoras de língua inglesa,de escola pública. Inicialmente, discutimos os conceitos de formaçãoreflexivo-crítica. Ademais, alguns aportes teóricos concernentes àGramática Sistêmico-Funcional (GSF) e à Análise Crítica do Discurso(ACD) são utilizados para subsidiar a análise das conversas colaborativasempreendidas pelas professoras. Ao final, algumas considerações acercada formação reflexivo-crítica são retomadas como sugestões para educadoresde língua estrangeira em cursos de formação continuada. PALAVRAS-CHAVE: formação continuada, língua estrangeira, formaçãoreflexivo-crítica CRITICAL-REFLECTIVE EDUCATION OF LANGUAGE TEACHERS: COLLABORATIVE CONVERSATIONS IN THE CONTEXT OF CONTINUING EDUCATION In this article we present the results of a research aboutcritical reflective education of three foreign language teachers from publicschool. In the beginning we talked about critical reflective educationconcepts. Moreover, we used some theoretical background of SystemicFunctional Grammar (SFG) and Critical Discourse Analysis (CDA) foranalyzing the discursive-linguistics aspects of the data, with some criticalreflections about the collaborative conversations undertaken by theteachers. At the end of the article, some considerations about criticalreflective education are retaken as some suggestions for foreign languageeducators during continuing education. KEYWORDS: continuing education, foreign language, critical reflectiveeducation